Restriction mapping of the genome of the protozoan parasite Theileria parva - Morzaria, S.P.; Young, J.R. (National Academy of Sciences, 1992)
We have used a modified linking clone strategy and pulsed-field gel electrophoresis to derive a map of the 29 Sfi I and 4 Not I sites in the 10 million base pair genome of the protozoan parasite Theileria parva. This was achieved in the absence of classical genetic information. The map reveals four chromosomes. Several genes, including those for parasite antigens, have been located on the map, as has the single locus carrying the major repetitive sequence in this organism. The map forms the basis for a study of sexual recombination in T. parva, which will be of importance in the application of present methods of immunization. Aspects of the mapping strategy may be useful in the study of other small eukaryotic genomes.